2010
DOI: 10.3177/jnsv.56.441
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus KT-11 Enhances Intestinal Immune Functions in C3H/HeN Mice

Abstract: SummaryWe investigated the effect of Lactobacillus crispatus KT-11 (KT-11) on intestinal immune systems in C3H/HeN mice. The level of intestinal total immunoglobulin (Ig) A was significantly higher in mice given KT-11 than in mice not given KT-11. Gene expression relating to antibody production and innate immune response increased more than 2-fold in the former compared with the later. Moreover, the number of IL-6 ϩ CD11bϩ cells was significantly higher in Peyer's patch cells cultured with KT-11 than in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Indeed, previous work has shown that treatment of mice with various strains of PBio lactobacilli spp. induced an increase in the level of IgA in the intestine (28, 29) and an increase in the frequency of small intestine IgA-expressing B cells (30). In order to assess whether PBio treatment with VSL#3 resulted in commensurate changes to Ig phenotype, we measured the frequency of B cells that expressed IgA versus IgG before and after PBio therapy using flow cytometry (Figure 2A, representative staining).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous work has shown that treatment of mice with various strains of PBio lactobacilli spp. induced an increase in the level of IgA in the intestine (28, 29) and an increase in the frequency of small intestine IgA-expressing B cells (30). In order to assess whether PBio treatment with VSL#3 resulted in commensurate changes to Ig phenotype, we measured the frequency of B cells that expressed IgA versus IgG before and after PBio therapy using flow cytometry (Figure 2A, representative staining).…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus crispatus K‐11 increased mucin 13 and defensin alpha genes expression in Peyer's patches by twofold compared with control, ensuring constant protection against the attack of digestive fluid, micro‐organisms, pollutants and toxins (Tobita et al . ). Moreover, the pili‐encoding operon spaABC of Lact.…”
Section: Mucosal Immune Systemmentioning
confidence: 97%
“…crispatus K‐11 did not influence the Th1/Th2 balance as illustrated by no change in the IFN‐ γ + CD4 + and IL‐4 + CD4 + cells in the normal C#H/HeN mice (Tobita et al . ). However, it reduced allergic symptoms by shifting the Th1/Th2 balance from Th2 dominant state to a Th1 dominant state in type I allergic model mice (Tobita et al .…”
Section: Systemic Immune Systemmentioning
confidence: 97%
“…bulgaricus species have been shown to be probiotic and are currently widely used in the food industry 2. Moreover, numerous studies have demonstrated that these probiotic Lactobacillus strains provide beneficial effects to the human immune system 3–5…”
Section: Introductionmentioning
confidence: 99%